The Meaning World of Guerrilla Marketing Campaigns through Semiotic Analysis - Nebi Seren; Fatih Bilici (İletişim Kuram ve Araştırma Dergisi)
Guerrilla marketing is an innovative and unconventional approach to advertising that aims to create a lasting impact on consumers through creativity and surprise. Unlike traditional advertising strategies, guerrilla marketing relies on symbolic and unexpected methods to attract consumer attention and increase brand engagement. This study aims to examine guerrilla marketing campaigns through semiotic analysis to reveal the impact of visual and textual elements in advertising content on consumer perception. The importance of this study lies in revealing how the symbols and meanings used in advertising shape consumer perception beyond the superficial appeal of advertisements. In this context, the study reveals how brands construct meaning through innovative advertising strategies and contribute to marketing communication. The study uses Roland Barthes' semiotic framework to evaluate the elements of literal meaning, connotation, metaphor and metonymy in guerrilla marketing advertisements. A purposive sampling technique was used in the study, and 21 advertisements from various sectors such as automotive, cosmetics, food, beverage and consumer goods were analyzed. The findings show that guerrilla marketing campaigns can effectively mobilize consumers through symbolic meanings, emotional triggers and cultural references. Moreover, the synergy of visual and verbal elements can increase message memorability and consumer engagement. This study provides a semiotic perspective on guerrilla marketing and offers practical suggestions for marketers and advertisers to design more effective campaigns.